The Effect of Ethanolic Extract of Salvia officinalis on the Uterine Natural Killer Cells Population at Day 7 of Pregnancy - N Beigi Boroujeni; M Beigi Boroujeni; E Rafiei Alavi; A Shafiei (Institue of Medicinal Plants, ACECR, 2015)
Background: Pregnancy is one of the changer agents for defensive cells, however it is unknown the effect of the ethanolic extract of the Salvia officinalis on the uterine Natural Killer cells population in the pregnant mice that needs to be investigated. Objective: The aim of this study was to determine the effect of the ethanolic extract of the Salvia officinalis on the uterine Natural Killer cells population. Methods: 10 female mice divided into two groups (control and test group). Mice in the control group mated with fertile male mice and mice in the test group received 100 mg/kg of the ethanolic extract of the Salvia officinalis once a day for 14 days, then mated with the fertile male mice. Mice in each group were examined at day 7 of pregnancy for ovarian hormones and evaluation of uterine Natural Killer cells. Results: Uterine Natural Killer cells population significantly decreased in the test group compare to the control group (p<0.05). Ovarian hormone levels (17-β estradiol and progesterone) were significantly increased in the test group comparison with the control group (p<0.05). Conclusion: It is concluded that decline in uterine Natural Killer cells population after treatment with the ethanolic extract of the Salvia officinalis could be due to hormonal changes that may be affect the implantation and embryo development.